Determinants of Smoking and Cessation Among Latinos: Challenges and Implications for Research - Castro, Yessenia (Soc Personal Psychol Compass, 2016)
Tobacco is a significant burden to individual and public health, and disparities exist among Latino smokers with respect to use and cessation. Although the prevalence of smoking is lower for Latinos than for non-Latino Whites and the general U.S. population, numerous health disparities exist within the population of Latino smokers. Much is known about determinants of smoking and cessation but the vast majority of this knowledge is based on research with non-Latino White smokers. This results in at least two important challenges in tobacco research among Latino smokers: (i) demonstrating the generalizability of known determinants of smoking and cessation, and; (ii) identifying culturally relevant variables that influence smoking and cessation among Latinos. An argument for increased research in these areas is presented with a review of existing research among Latino smokers that demonstrates these needs. Research is summarized that suggests socioeconomic position, depressive symptomatology, physical dependence, and gender function differently as determinants of smoking and cessation among Latinos compared with the general population of smokers. Research is also reviewed that suggests the promise of acculturation, acculturative stress, and discrimination as culturally relevant determinants of smoking and cessation. Research and practice implications are discussed, and specific areas for future research are offered.